Myeloid cell reprogramming alleviates immunosuppression and promotes clearance of metastatic lesions - Raghani, Ravi M.; Ma, Jeffrey A.; Zhang, Yining; Orbach, Sophia M.; Wang, Jing; Zeinali, Mina; Nagrath, Sunitha; Kakade, Sandeep; Xu, Qichen; Podojil, Joseph R.; Murthy, Tushar; Elhofy, Adam; et al. (Frontiers in Oncology, 2022)
Suppressive myeloid cells, including monocyte and neutrophil populations, play a vital role in the metastatic cascade and can inhibit the anti-tumor function of cytotoxic T-cells. Cargo-free polymeric nanoparticles (NPs) have been shown to modulate innate immune cell responses in multiple pathologies of aberrant inflammation. Here, we test the hypothesis that the intravenous administration of drug-free NPs in the 4T1 murine model of metastatic triple-negative breast cancer can reduce metastatic colonization of the lungs, the primary metastatic site, by targeting the pro-tumor immune cell mediators of metastatic progression. In vivo studies demonstrated that NP administration reprograms the immune milieu of the lungs and reduces pulmonary metastases. Single-cell RNA sequencing of the lungs revealed that intravenous NP administration alters myeloid cell phenotype and function, skewing populations toward inflammatory, anti-tumor phenotypes and away from pro-tumor phenotypes. Monocytes, neutrophils, and dendritic cells in the lungs of NP-treated mice upregulate gene pathways associated with IFN signaling, TNF signaling, and antigen presentation. In a T-cell deficient model, NP administration failed to abrogate pulmonary metastases, implicating the vital role of T-cells in the NP-mediated reduction of metastases. NPs delivered as an adjuvant therapy, following surgical resection of the primary tumor, led to clearance of established pulmonary metastases in all treated mice. Collectively, these results demonstrate that the in vivo administration of cargo-free NPs reprograms myeloid cell responses at the lungs and promotes the clearance of pulmonary metastases in a method of action dependent on functional T-cells.